2016
DOI: 10.1016/j.ecolind.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trade openness on global carbon dioxide emissions: Evidence from the top ten emitters among developing countries

Abstract: This study aims to analyze the relationship between carbon dioxide (CO2) emissions, trade openness, real income and energy consumption in the top ten CO2 emitters among the developing countries; namely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
154
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(170 citation statements)
references
References 111 publications
(141 reference statements)
15
154
0
1
Order By: Relevance
“…Secondly, international trade can accelerate or hamper the pace of carbon emission as it influences both domestic production and foreign consumption (Al-Mulali, Ozturk, & Lean, 2015;Bento & Moutinho, 2016;Ertugrul, Cetin, Seker, & Dogan, 2016;Kanemoto, Moran, Lenzen, & Geschke, 2014;Lau et al, 2014;Ren, Yuan, Ma, & Chen, 2014). Also, the concept of carbon emission embodied in trade has also been an increasingly observed phenomenon (Böhringer, Carbone, & Rutherford, 2018;Sakai & Barrett, 2016;Su & Ang, 2014;Wu, R., Geng, Dong, Fujita, & Tian, 2016;Yunfeng & Laike, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, international trade can accelerate or hamper the pace of carbon emission as it influences both domestic production and foreign consumption (Al-Mulali, Ozturk, & Lean, 2015;Bento & Moutinho, 2016;Ertugrul, Cetin, Seker, & Dogan, 2016;Kanemoto, Moran, Lenzen, & Geschke, 2014;Lau et al, 2014;Ren, Yuan, Ma, & Chen, 2014). Also, the concept of carbon emission embodied in trade has also been an increasingly observed phenomenon (Böhringer, Carbone, & Rutherford, 2018;Sakai & Barrett, 2016;Su & Ang, 2014;Wu, R., Geng, Dong, Fujita, & Tian, 2016;Yunfeng & Laike, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, the energy consumption in the CPUA region is mainly caused by coal burning, which generates high levels of industrial SO 2 and dust. Technological investment represents the level of regional science and technology [15,18]. The higher the technological investment, the more effective the production mode.…”
Section: Data Collection and Variable Descriptionmentioning
confidence: 99%
“…They found that China's energy and electricity consumption and per capita gross domestic product (GDP) presented an inverted N-type EKC. Ertugrul et al [18] studied the relationship between per capita income and energy consumption in the major developing countries. The results showed that the EKC hypothesis applied best to the countries with fast economic growth, such as China.…”
Section: Environmental Kuznets Curve With Spatial Econometricsmentioning
confidence: 99%
“…Burke [5] investigated carbon dioxide emissions from the combustion of fossil fuels and the manufacture of cement. The works of Tan [6] and Ertugrul [7] provided several extensive studies on the calculation of carbon emissions. A plausible method of computer modeling combining genetic algorithms and a chemical reactor network was developed by Christopher [8] to predict alternative fuel gaseous emissions.…”
Section: Introductionmentioning
confidence: 99%